2001
DOI: 10.1089/089771501317095313
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Leukemia Inhibitory Factor in Human Nerve following Injury

Abstract: In animal models of peripheral nerve injury, leukemia inhibitory factor (LIF) is normally expressed at very low levels. Following nerve injury, its expression is rapidly increased in the nerve at the injury site and promotes both sensory and motor neuron survival. Once normal nerve function is restored, LIF expression returns to negligible levels. For this reason, LIF is considered to be a peripheral nerve trauma factor. We wished to determine whether LIF is also upregulated in human nerves following trauma an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…LIF is a stable compound that promotes neuronal survival in animal models of neurodegeneration 37 . It was reported that, although LIF is normally expressed at very low levels, its expression is rapidly increased in the nerve following injury, and that it promotes both sensory and motor neuron survival 38 . The abundant expression of LIF receptors on motor neurons and the increase of retrograde axonal transport of LIF by motor neurons following peripheral nerve injury were reported 39 .…”
Section: Discussionmentioning
confidence: 99%
“…LIF is a stable compound that promotes neuronal survival in animal models of neurodegeneration 37 . It was reported that, although LIF is normally expressed at very low levels, its expression is rapidly increased in the nerve following injury, and that it promotes both sensory and motor neuron survival 38 . The abundant expression of LIF receptors on motor neurons and the increase of retrograde axonal transport of LIF by motor neurons following peripheral nerve injury were reported 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it can induce several neuropeptides through alteration of neuronal gene expression (Patterson and Nawa, 1993) known to be involved in the response of neural tissue to injury (Sun et al, 1996). LIF is retrogradely transported to the cell body of spinal motoneurons and rapidly upregulated when nerve injury occurs (Curtis et al, 1994;Dowsing et al, 2001). LIF also protects facial motoneurons from axotomyinduced cell death (Hughes et al, 1993) and promotes regeneration after nerve injury (Tham et al, 1997;Cafferty et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…LIF is expressed at very low levels throughout the body, but increases following brain injury (Banner et al, 1997) and stroke . Its expression in injured peripheral nerves is decreased again after repair (Dowsing et al, 2001), perhaps coincident with re-establishment of vascular integrity. The mechanisms regulating LIF expression are not well understood, but may include stimulation by IL-1β, possibly through mRNA stabilization (Carlson et al, 1996).…”
Section: Introductionmentioning
confidence: 99%